Vliyaniye pordol'zhitel'nosti vol'nykh skhvatok na razvitiye rabotosposobnostu bortsov - Eliseev, S. V.; Kulik, N. G. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
It was studied how training fights could be used for the development of performance capacity in sambo and which is the influence of the duration of these fights.